SOCIAL AND CULTURAL ASPECTS OF GLOBALIZATION FOR THE ECONOMY OF UZBEKISTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article examines the issues of the economic nature of globalization, its positiveand negative consequences for the economy and social structure. The socio-cultural consequencesof labor migration as one of the main manifestations of globalization are considered and ways toreduce the negative consequences of globalization are proposed.
Keywords: Globalization, economic benefits and costs, social consequences, cultural aspects, migration.